Performance of castor-based intercropping in semi-arid zone of Haryana: PERFORMANCE OF CASTOR-BASED INTERCROPPING IN SEMI-ARID ZONE OF HARYANA - K GANGADHAR; J S YADAV; ANIL KUMAR YADAV (Journal of Oilseeds Research, 2024)
To enhance the productivity of castor per unit area and over time, a study was conducted during the kharif 2020-21 season at the Regional Research Station, CCS HAU, Bawal,. The study aimed to evaluate the compatibility, production potential, and optimal row proportions of component crops in intercropping systems involving castor. The field investigation was carried out to identify suitable intercrops for maximizing castor yield and analyse the economic viability of various treatments under two different row spacing for castor: 150 cm and 200 cm. The results indicated that the highest castor seed and stalk yield were achieved in sole castor (3,879 kg/ha and 5,656 kg/ha, respectively) with 200 cm row spacing, a similar performance was observed with a 150 cm row spacing. Further, intercropping of castor (150 cm) + mungbean (1:2) recorded higher seed yield (3,547 kg/ha) and stalk yield (5,248 kg/ha), highest castor equivalent yield (4,220 kg/ha) and land equivalent ratio (1.53) and resulted in higher economic returns with a benefit-cost ratio of 3.78.